2012
DOI: 10.1038/psp.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Kinetic Modeling of Liposomal Doxorubicin Delivery Quantifies the Role of Tumor and Drug‐Specific Parameters in Local Delivery to Tumors

Abstract: Nanoparticle encapsulation has been used as a means to manipulate the pharmacokinetic (PK) and safety profile of drugs in oncology. Using pegylated liposomal doxorubicin (PLD) vs. conventional doxorubicin as a model system, we developed and experimentally validated a multiscale computational model of liposomal drug delivery. We demonstrated that, for varying tumor transport properties, there is a regimen where liposomal and conventional doxorubicin deliver identical amounts of doxorubicin to tumor cell nuclei.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Doxorubicin cellular transport is modeled on the basis of published work (34,35). Free doxorubicin partitions into the outer leaflet of the plasma membrane, characterized by association rate constant k f_ol , cell surface area (based on cell radius, assuming spherical cells), and a partition coefficient.…”
Section: Kinetic Computational Modelmentioning
confidence: 99%
“…Doxorubicin cellular transport is modeled on the basis of published work (34,35). Free doxorubicin partitions into the outer leaflet of the plasma membrane, characterized by association rate constant k f_ol , cell surface area (based on cell radius, assuming spherical cells), and a partition coefficient.…”
Section: Kinetic Computational Modelmentioning
confidence: 99%
“…This exercise suggested that inhibitors of TrkA kinase may be an interesting approach for novel pain medications, but highlights that achieving saturating inhibition may require higher unbound plasma drug concentrations than might be expected according to simple pharmacological theory. Data-validated systems pharmacology models such as described in this study (and in other areas such as central nervous system diseases [33], oncology [34], osteoporosis [35], endometriosis [9] and safety [36]) could be of great utility in drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…If this relationship holds true in a larger population, it would suggest that deposition may be a dominant factor for response to nal-IRI in certain tumor types. The importance of lesion permeability for liposomal delivery has been shown in preclinical tumor models (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis found that pharmacokinetic properties and permeability of the tumor vasculature to nal-IRI positively affected duration of SN-38 in tumors. Liposomal deposition in tumors was also found to be a rate-limiting step for drug delivery to cells for other long-circulating liposomes (16). It has previously been shown that tumor deposition of a liposomal contrast agent correlated with treatment outcome to a liposomal drug in a rat xenograft model (17).…”
Section: Introductionmentioning
confidence: 99%